Evaluación de Impacto del Programa de Microcrédito del Banco ProCredit en la ciudad de Quito, en el período 2009-2012. - Vaca Pérez, Leticia Andrea (2014)
This study shows the impact that microcredit has had on the lives of those who receive it. In particular, it focuses on the evaluation of the impact it has had the microcredit program ProCredit Bank in the period 2009-2012 when achieve its main objective, namely the improvement and socio-economic and financial integration of its customers and the bank itself. ProCredit Bank in order to support viable social economy initiatives and self employment, that combined, in turn, the social integration of vulnerable people with business efficiency and profitability. This evaluation gives results of growth with a focus on the contribution Microenterprise, microenterprise development and economic participation at the bank level, financial and governmental system.